Effect of hydrochlorothiazide on the pharmacokinetics and pharmacodynamics of febuxostat, a non-purine selective inhibitor of xanthine oxidase - Grabowski, Brian (Blackwell Science Inc, 2010)
AIM: This study examined the effect of co-administration of febuxostat, an investigational urate lowering therapy, and hydrochlorothiazide on the pharmacokinetics and pharmacodynamics of febuxostat. METHODS: Healthy subjects (36 healthy men and women) received single doses of febuxostat 80 mg alone and febuxostat 80 mg + hydrochlorothiazide 50 mg, separated by 7 days in an open-label, randomized, crossover fashion. Plasma concentrations of febuxostat and urinary and serum concentrations of uric acid were assessed. RESULTS: Mean febuxostat C(max), AUC((0–t)), AUC((0–∞)), t(1/2,z), CL/F and V(ss)/F values for regimens co-administration/febuxostat alone were 2.9/2.9 µg ml(−1), 9.3/9.1 µg ml(−1) h, 9.6/9.3 µg ml(−1) h, 6.5/6.1 h, 8.8/9.3 l h(−1) and 45/44 l, respectively. Geometric mean ratios (co-administration : febuxostat alone) and their 90% confidence intervals for febuxostat plasma C(max), AUC((0–t)), and AUC((0–∞)) were 1.00 (0.86, 1.17), 1.03 (0.98, 1.09), and 1.04 (0.98, 1.10), respectively; all of the 90% CIs were within the no effect range of 0.8 to 1.25. Serum uric acid C(mean,24h), C(mean,48h) and CL(R) for both regimens co-administration/febuxostat alone were 216/203 µmol l(−1), 218/202 µmol l(−1) and 9.1/10.1 ml min(−1), respectively. Although serum uric acid C(mean,24h) and C(mean,48h) values were higher and CL(R) values lower after co-administration compared with dosing of febuxostat alone, with the differences being statistically significant (P < 0.003), none of the differences (6.5%–9.5%) was considered clinically significant. CONCLUSION: Dose adjustment for febuxostat is not necessary when it is administered with hydrochlorothiazide.